Preparation method of efficient and stable rare earth titanium oxygen cluster luminescent material

By adopting the rare earth titanium oxide cluster luminescent material preparation method of [C90H56O26N4F10Ln2Ti4], the problems of low absorption cross-section and difficulty in synthesis control of nanoscale materials in the prior art are solved, and efficient and stable preparation of luminescent materials and multi-band output are achieved.

CN119390721APending Publication Date: 2025-02-07YILI NORMAL UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411603479.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

There is a problem of low absorption cross-section among existing compounds based on trivalent lanthanides, which leads to difficulty in direct excitation, and it is difficult to achieve atomic precise synthesis control and uniform particle diameter during the synthesis process of nanoscale molecular cluster luminescent materials. distributed.

Method used

Using [C90H56O26N4F10Ln2Ti4], a rare earth titanium oxide cluster luminescent material that is surrounded by an outer tunable multi-dentate organic ligand, is used to achieve efficient and stable materials through steps such as sonication and heating treatment. preparation.

Benefits of technology

This method can prepare rare earth titanium oxide cluster luminescent materials with high-efficiency luminescent ability, strong repeatability and good stability without high temperature and high pressure, and can achieve multi-band output by doping different lanthanide elements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119390721A_ABST
    Figure CN119390721A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of chemistry, and discloses a preparation method of an efficient and stable rare earth titanium oxygen cluster luminescent material, and the chemical formula of the efficient and stable rare earth titanium oxygen cluster luminescent material is [C90H56O26N4F10Ln2Ti4], the preparation method comprises the following steps: weighing raw materials according to a chemical formula ratio, and adding the raw materials into an acetonitrile solution to form a mixed solution; adding titanium isopropoxide, sealing, treating in an ultrasonic machine until the materials are fully mixed, and then filtering; heating the filtered clarified solution to separate out blocky crystals, and taking out the blocky crystals after cooling; the preparation method provided by the invention has the advantages that the operation is simple, the energy consumption is low, and harsh synthesis environments such as high temperature and high pressure are not needed; the cluster material prepared by the method has a crystal structure, high-efficiency luminescence capability, strong repeatability and good stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of chemical technology, and in particular to a method for preparing a highly efficient and stable rare earth titanium oxide cluster luminescent material. Background Art

[0002] Lanthanide ions are well known for their extraordinary multifunctional luminescent properties. In recent years, lanthanum-based nanomaterials have occupied an important position in various luminescent materials developed by humans. Most trivalent lanthanide ions (Ln 3+ ) is typical of the luminescence from the partially filled 4f n An essential characteristic of lanthanide elements is that the 4f orbital is replaced by the 5s 2 5p 6 The subshell is shielded, thus forming an inner orbital feature. This remarkable feature leads to the unique optical properties of lanthanides and results in particularly sharp absorption and emission lines unique to each lanthanide, and the emission region can cover the spectral region from the visible light region to the near-infrared region. However, there are still various problems in compounds based on trivalent lanthanides. First, the ff transition forbidden of lanthanide ions leads to low absorption cross-sections, making direct excitation difficult; in addition, the optical properties of trivalent lanthanide ions are closely related to the coordination environment around them. In this case, in order to solve the problem of low absorption cross-section to a certain extent and to place the trivalent lanthanide ions as the luminescence center in a suitable crystal field environment, it is necessary to find a system that can open the forbidden transition to a certain extent and construct an effective energy transfer process to enhance the luminescence performance of trivalent lanthanide compounds.

[0003] In previous work, scientists have widely used the "antenna effect", i.e., ligand-mediated intramolecular electron transfer, to solve the problem of low absorption cross-section. This strategy relies on using an organic compound, which usually has a larger absorption cross-section, to absorb light and transfer it to the Ln 3+ The lanthanide center can effectively absorb energy under low-power excitation, significantly enhancing the luminescence of the lanthanide. Although the transition forbidden zone can be opened to a certain extent to solve the problem of low absorption cross section, in the previous nanoparticle synthesis process, it is still a major challenge to obtain uniform particle size distribution while achieving precise synthesis control at the atomic level. At this time, the preparation of nanoscale molecular cluster luminescent materials may be the optimal solution to this problem. [C 90 H 56 O 26 N4F 10Ln2Ti4] This rare earth titanium oxide cluster luminescent material, which is composed of an outer tunable multi-tooth organic ligand as an emission antenna and wraps around an inner multi-core inorganic metal luminescent center, can open the transition forbidden zone to a certain extent to increase the absorption cross section, and at the same time obtain a uniform particle size distribution under precise synthesis control at the atomic level. Due to the similarity of trivalent lanthanides in chemical reactions, it is possible to dope different trivalent lanthanides in a molecular cluster, so the size and number of rare earth titanium oxide clusters can be customized by controlling the synthesis conditions, precursor materials and template strategies. Summary of the invention

[0004] The purpose of the present invention is to solve the shortcomings of the prior art and to propose a method for preparing a highly efficient and stable rare earth titanium oxide cluster luminescent material.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions: A method for preparing a highly efficient and stable rare earth titanium oxide cluster luminescent material, wherein the chemical formula of the highly efficient and stable rare earth titanium oxide cluster luminescent material is: 90 H 56 O 26 N4F 10 Ln2Ti4]; The preparation method comprises the following steps: Step 1: Weigh the required mass of each reaction raw material according to the atomic ratio of each element in the chemical formula; Step 2: Add the reaction raw materials weighed in step 1 to the acetonitrile solution, shake until the solid is dissolved, and obtain a mixed solution; Step 3: adding isopropyl titanate to the mixed solution obtained in step 2 and sealing; Step 4: placing the mixed solution obtained in step 3 in an ultrasonic machine for ultrasonic treatment until it is fully mixed, and then filtering the mixed solution; Step 5: Place the filtered clarified solution in a sealed container, heat it, and block crystals will precipitate in the container, and then take it out after naturally cooling to room temperature; Step 6: Wash the bulk crystals obtained in step 5 to obtain the highly efficient and stable rare earth titanium oxide cluster luminescent material.

[0006] Preferably, the lanthanide elements in the chemical formula include Eu, Gd, and Nd.

[0007] Preferably, in step 2, the water content of the acetonitrile solution used is less than 0.1%.

[0008] Preferably, in step 4, the solution is filtered using a nylon filter with a pore size of 0.45 μm.

[0009] Preferably, in step 5, the specific method of heating treatment is: heating treatment at 70° C. for 24 hours.

[0010] Preferably, in step 6, the cleaning of the block crystals is repeated no more than 3 times.

[0011] The beneficial effects of the present invention are: The invention provides a method for preparing a highly efficient and stable rare earth titanium oxide cluster luminescent material, which is simple to operate, has low energy consumption, and does not require harsh synthesis environments such as high temperature and high pressure. The cluster material prepared by the method has a crystal structure, has highly efficient luminescence ability, strong repeatability, and good stability.

[0012] The present invention proposes a method for preparing a highly efficient and stable rare earth titanium oxide cluster luminescent material, in which two organic ligands, p-fluorobenzoic acid and bipyridine, are used as the outer tunable high absorption antenna, which wraps the inner 6-core inorganic metal luminescent center. Due to the similarity of trivalent lanthanide elements in chemical reactions, we can customize homogeneous metal and heterogeneous metal materials with different luminescent bands according to the luminescent characteristics of each element, wherein the fluorescence quantum yield of homogeneous metal reaches 90%, and heterogeneous metal materials can achieve multi-band output from visible light to near-infrared light through doping. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 For [C 90 H 56 O 26 N4F 10 Schematic diagram of the structure of Ln2Ti4], including multidentate organic ligands and metal luminescent centers.

[0014] Figure 2 For [C 90 H 56 O 26 N4F 10 XRD pattern of Ln2Ti4] single crystal structure.

[0015] Figure 3 For [C 90 H 56 O 26 N4F 10 Emission spectrum of Eu2Ti4]{Eu2Ti4}.

[0016] Figure 4 For [C 90 H 56 O 26 N4F 10 Excitation spectrum of Eu2Ti4]{Eu2Ti4}.

[0017] Figure 5 For [C 90 H56 O 26 N4F 10 Fluorescence decay curve of Eu2Ti4]{Eu2Ti4}.

[0018] Figure 6 Nd 3+ Exists in [C 90 H 56 O 26 N4F 10 Nd2Ti4]{Nd2Ti4} produces near-infrared emission spectrum.

[0019] Figure 7 This is a stability test of rare earth titanium oxide cluster luminescent materials. DETAILED DESCRIPTION

[0020] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.

[0021] In the present application, the chemical formula of the highly efficient and stable rare earth titanium oxide cluster luminescent material is: 90 H 56 O 26 N4F 10 Ln2Ti4]; The method for preparing the highly efficient and stable rare earth titanium oxide cluster luminescent material comprises the following steps: Step 1: Weigh the required mass of each reaction raw material according to the atomic ratio of each element in the chemical formula; Step 2: Add the reaction raw materials weighed in step 1 to the acetonitrile solution, shake until the solid is dissolved, and obtain a mixed solution; Step 3: adding isopropyl titanate to the mixed solution obtained in step 2 and sealing; Step 4: The mixed solution obtained in step 3 is placed in an ultrasonic machine for ultrasonic treatment until it is fully mixed, and then the mixed solution is filtered using a nylon filter with a pore size of 0.45 μm; Step 5: Place the filtered clarified solution in a sealed container and heat it at 70°C for 24 hours. Block crystals will precipitate in the container and then be taken out after naturally cooling to room temperature. Step 6: Wash the bulk crystals obtained in step 5 to obtain the highly efficient and stable rare earth titanium oxide cluster luminescent material.

[0022] Example 1: Preparation of [C 90 H 56 O 26 N4F 10 Eu2Ti4]{Eu2Ti4} Step 1: Calculate the required mass of each reaction raw material, europium acetate (0.05mmol, 16.4mg), p-fluorobenzoic acid (0.5mmol, 70mg); 2'2-bipyridine (0.15mmol, 24mg); Step 2: Weigh the amount of each reactant according to the result calculated in step 1. Here, you need to pay close attention to the water content of the reaction raw materials; Step 3: Add the weighed reaction raw materials into 6 mL of acetonitrile solution and shake to completely dissolve the solid to obtain a mixed solution; Step 4: Add 36uL of isopropyl titanate to the mixed solution obtained in step 3 and quickly cover the bottle cap; Step 5: placing the mixed solution obtained in step 4 in an ultrasonic machine for ultrasonic treatment for 30 minutes, with the ultrasonic temperature controlled at about 25° C. to allow it to fully dissolve and obtain a mixed solution; Step 6: Filter the mixed solution obtained in step 5 using a nylon filter; Step 7: Place the filtered clarified solution in a sealed explosion-proof glass bottle and heat it at 70°C for 24 hours. Block crystals will grow at the bottom of the bottle. Take it out after naturally cooling to room temperature. Step 8: Add an appropriate amount of acetonitrile to the mixture containing block crystals and complex impurities for forming crystals obtained in step 7, shake on a mixer to allow the crystals adsorbed on the wall of the quartz glass bottle to sink to the bottom of the bottle, and at the same time dissolve the complex impurities, use a dropper to suck out the upper solution, repeat the above operation to remove impurities attached to the surface of the crystal, and then place in an oven, and dry at 30°C in a vacuum environment to obtain a pure molecular cluster luminescent material.

[0023] Example 2: Preparation of [C 90 H 56 O 26 N4F 10 Gd2Ti4]{Eu2Ti4} Step 1: Calculate the required mass of each reaction raw material, gadolinium acetate (0.05mmol, 16.4mg), p-fluorobenzoic acid (0.5mmol, 70mg); 2'2-bipyridine (0.15mmol, 24mg); Step 2: Weigh the amount of each reactant according to the result calculated in step 1. Here, you need to pay close attention to the water content of the reaction raw materials; Step 3: Add the weighed reaction raw materials into 6 mL of acetonitrile solution and shake to completely dissolve the solid to obtain a mixed solution; Step 4: Add 36uL of isopropyl titanate to the mixed solution obtained in step 3 and quickly cover the bottle cap; Step 5: placing the mixed solution obtained in step 4 in an ultrasonic machine for ultrasonic treatment for 30 minutes, with the ultrasonic temperature controlled at about 25° C. to allow it to fully dissolve and obtain a mixed solution; Step 6: Filter the mixed solution obtained in step 5 using a nylon filter; Step 7: Place the filtered clarified solution in a sealed explosion-proof glass bottle and heat it at 70°C for 24 hours. Block crystals will grow at the bottom of the bottle. Take it out after naturally cooling to room temperature. Step 8: Add an appropriate amount of acetonitrile to the mixture containing block crystals and complex impurities for forming crystals obtained in step 7, shake on a mixer to allow the crystals adsorbed on the wall of the quartz glass bottle to sink to the bottom of the bottle, and at the same time dissolve the complex impurities, use a dropper to suck out the upper solution, repeat the above operation to remove impurities attached to the surface of the crystal, and then place in an oven, and dry at 30°C in a vacuum environment to obtain a pure molecular cluster luminescent material.

[0024] Example 3: Preparation of [C 90 H 56 O 26 N4F 10 Nd2Ti4]{Nd2Ti4} Step 1: Calculate the required mass of each reaction raw material, neodymium acetate (0.05mmol, 21.2mg), p-fluorobenzoic acid (0.5mmol, 70mg); 2'2-bipyridine (0.15mmol, 24mg). Step 2: Weigh the amount of each reactant according to the result calculated in step 1. Here, you need to pay close attention to the water content of the raw materials. Step 3: Add the weighed reaction raw materials into 6 mL of acetonitrile solution and shake to completely dissolve the solid to obtain a mixed solution; Step 4: Add 36uL of isopropyl titanate to the mixed solution obtained in step 3 and quickly cover the bottle cap; Step 5: placing the mixed solution obtained in step 4 in an ultrasonic machine for ultrasonic treatment for 30 minutes, with the ultrasonic temperature controlled at about 25° C. to allow it to fully dissolve and obtain a mixed solution; Step 6: Filter the mixed solution obtained in step 5 using a nylon filter; Step 7: Place the filtered clarified solution in a sealed explosion-proof glass bottle and heat it at 70°C for 24 hours. Block crystals will grow at the bottom of the bottle. Take it out after cooling naturally to room temperature. Step 8: Add an appropriate amount of acetonitrile to the mixture containing block crystals and complex impurities for forming crystals obtained in step 7, shake on a mixer to allow the crystals adsorbed on the wall of the quartz glass bottle to sink to the bottom of the bottle, and at the same time dissolve the complex impurities, use a dropper to suck out the upper solution, repeat the above operation to remove impurities attached to the surface of the crystal, and then place in an oven, and dry at 30°C in a vacuum environment to obtain a pure molecular cluster luminescent material.

[0025] The crystal structure obtained by synthesis is as follows Figure 1 As shown in Figure 2, the nanoscale cluster material containing two lanthanide metal luminescence centers and four transition metals synthesized by this method has a symmetrical structure with a short distance between the metal centers. The diffraction information is as follows: Figure 1 As shown, it is possible to carry out large-scale synthesis with considerable yields and without purification. Figure 3 As shown, this method synthesized [C 90 H 56 O 26 N4F 10 Eu2Ti4] has significant red light emission. Figure 4 As shown, this system can effectively sensitize Eu 3+ .like Figure 5 As shown, this method synthesized [C 90 H 56 O 26 N4F 10 The quantum yield of Eu2Ti4 is as high as 87%, indicating that the system can effectively suppress non-radiative transitions. Figure 6 As shown, this method synthesized [C 90 H 56 O 26 N4F 10 Nd2Ti4] can produce Nd 3+ The characteristic emission of the metal luminescent center indicates that the full-band light output from visible to near-infrared can be achieved by controlling the composition of the metal luminescent center. Figure 7 As shown, this material still exhibits luminescence characteristics with almost no attenuation after being stored for one year, indicating that this rare earth titanium oxide cluster material has excellent stability.

[0026] The present invention provides a method for preparing a rare earth titanium oxide cluster material with efficient and stable luminescence characteristics by using rare earth acetate. This material system uses p-fluorobenzoic acid as a highly absorptive ligand antenna, and the components thereof can be flexibly customized according to demand to achieve luminescence in different bands. Two metal luminescence centers that are relatively close can generate abundant interactions, and the material has good stability.

[0027] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A method for preparing an efficient and stable rare earth titanium oxide cluster luminescent material, characterized in that: The chemical formula of the highly efficient and stable rare earth titanium oxide cluster luminescent material is: 90 H 56 O 26 N4F 10 Ln2Ti4]; The preparation method comprises the following steps: Step 1: Weigh the required mass of each reaction raw material according to the atomic ratio of each element in the chemical formula; Step 2: Add the reaction raw materials weighed in step 1 to the acetonitrile solution, shake until the solid is dissolved, and obtain a mixed solution; Step 3: adding isopropyl titanate to the mixed solution obtained in step 2 and sealing; Step 4: placing the mixed solution obtained in step 3 in an ultrasonic machine for ultrasonic treatment until it is fully mixed, and then filtering the mixed solution; Step 5: Place the filtered clarified solution in a sealed container, heat it, and block crystals will precipitate in the container, and then take it out after naturally cooling to room temperature; Step 6: Wash the bulk crystals obtained in step 5 to obtain the highly efficient and stable rare earth titanium oxide cluster luminescent material.

2. The method for preparing a highly efficient and stable rare earth titanium oxide cluster luminescent material according to claim 1, characterized in that: The lanthanoid elements in the chemical formula include Eu, Gd, and Nd.

3. The method for preparing a highly efficient and stable rare earth titanium oxide cluster luminescent material according to claim 1, characterized in that: In step 2, the water content in the acetonitrile solution used is less than 0.1%.

4. The method for preparing a highly efficient and stable rare earth titanium oxide cluster luminescent material according to claim 1, characterized in that: In step 4, the solution is filtered using a nylon filter with a pore size of 0.45 μm. 5 . The method for preparing a highly efficient and stable rare earth titanium oxide cluster luminescent material according to claim 1 , wherein in step 5, the specific method of the heat treatment is: heating the material at 70° C. for 24 hours.

6. The method for preparing a highly efficient and stable rare earth titanium oxide cluster luminescent material according to claim 1, characterized in that: In step 6, the cleaning of the block crystal is repeated no more than 3 times.

Citation Information

Patent Citations

  • Synthesis and applications of inorganic-organic hybrid europium phosphate photochromic material

    CN110357910A

  • Novel fluorescent ink and preparation method and application thereof

    CN113061368A

  • Efficient and stable lanthanide molecular cluster luminescent material and preparation method thereof

    CN117683054A

  • Wavelength downconverters

    WO2024194652A1